Ideal city from the perspective of children through participatory planning – Duhok City in Kurdistan Region of Iraq - Mohammed, Jambally; Al-Doski, Diman (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
As urban expansion proceeds rapidly world-wide, challenges to urban planning and public participation become more conspicuous. Urbanization, and particularly rapid urban expansion, has serious implications for children. While this age group is most vulnerable to the environmental hazards of cities, their needs are rarely given a special focus. Children are seldom involved in planning and decision-making on matters that touch their lives. The focus of local governments is rather on how to provide enough employment opportunities, transport, housing and other basic services to meet the growing needs. This article aims to capture the perceptions of children from two schools in Duhok city, Kurdistan Region of Iraq (KRI) about the desired spatial environment in which they want to live. For this purpose, participatory mapping was used as a tool, whereby the children were able to express their needs and preferences through drawing/mapping their ideal cities. In preparation for the drawing exercise, the children had acquired a basic understanding of city planning and the basic elements that constitute the image of a city, based on Kevin Lynch’s (1960, 1977) theory of the elements of a city image. The contents of the children’s drawings were subsequently analyzed, based on Roger A. Hart’s (2011) classification of eight city models. The results show that the majority of the city maps drawn by the children have the characteristics of the safe and accessible city. This study does not only explore children’s perceptions of their existing and future urban environments, but also constitutes a unique initiative to encourage the involvement of school children of a Middle Eastern country in an informal city planning practice.